Kekerasan atas Nama Agama vis a vis Amar Makruf Nahi Mungkar - Hasan Su'aidi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2012)
Harshness on behalf of religion, through the idiom of Amar makruf nahi mungkar, is frequently vague (similar but different.) The spirit to blindly perform Amar makruf nahi mungkar (with haphazardly act) will fīnally result harshness. Instead of accomplishing religious teaching, it even would break its teachings themselves. Therefore, intact understanding towards the teaching of amr ma‘rūf and nahy munkaris strongly required, in support of avoiding harshness which uses religion. Ḥadīth, as a basic of religion, is so often understood without integral comprehension. Consequently, ‘harshness’ within amar makruf nahi mungkar is perceived as indication of a person’s strong faith, and the only way to perform amar makruf nahi mungkar. This writing tries to give proportional understanding of amar makruf nahi mungkar which is taught by the religion and is different from the religious harshness.DOI: 10.15408/ref.v13i3.903